Telegram (copy) - Citrine, Walter, 1887-1983
011-0011-001 COPY OF TELEGRAM SENT TO I.F.T.U. ON 9 DECEMBER. 1937 SCHEVENELS, INTERFED, PARIS. IMPOSSIBLE FOR ME TO VISIT SPAIN BEFORE NEW YEAR STOP WOULD SUGGEST JANUARY THIRD TO TENTH STOP IF DATES UNSUITABLE WOULD BE QUITE WILLING FOR OTHER EXECUTIVE MEMBERS TO FORM DELEGATION. CITRINE. 292/946/11/11